Navigating pedagogical choices: Teacher decision-making in remote learning environment - Atti Herawati; Setiono Sugiharto; Christine Manara (Teaching English as a Foreign Language Journal, 2026)
Decision-making is the fundamental teaching skill that is enacted in practice. The exploration of pedagogical decision-making by teachers in remote instructional settings offers valuable theoretical insights and practical contributions to the field of English Language Teaching (ELT). Thus, this study was aimed at exploring pedagogical decisions teachers make in their remote teaching practices. A qualitative, exploratory approach was employed, and virtual observation through Zoom Meeting or Google Meet served as the main data collection instrument. Five lecturers from five different private universities in West Java, Indonesia participated in this study, a sample size consistent with the in-depth, interpretive nature of qualitative inquiry. Observation notes and video transcripts were analysed using grounded theory through three coding stages. The study revealed that the majority of instructional decisions were strategically oriented toward maintaining student engagement and promoting seamless lesson progression. Translanguaging was dominant and employed by all participants. Among five decision types (rational, intuitive, dependent, avoidant, and spontaneous), spontaneous decision-making emerged as the most commonly utilized, in contrast to dependent and avoidant decisions, which occurred with considerably lower frequency. These findings contribute theoretically to the understanding of teacher cognition in digital contexts and practically to the preparation of teachers for responsive, reflective decision-making in remote ELT.